DETERMINAN KEPUTUSAN PEMBELIAN DITINJAU DARI ASPEK EKUITAS MEREK DAN KUALITAS PRODUK - Setya Mariana; Veny Puspita; Melvi Yansi (Yayasan Insani Mandiri Santani, 2026)
This study aims to determine the influence of brand equity and product quality on motorcycle purchase decisions at the Astra Honda Dealership in Tanah Patah, Bengkulu City. This research is motivated by the highly competitive automotive industry, which requires companies to build strong brand equity and maintain product quality to enhance consumer purchasing decisions. The independent variables in this study are brand equity and product quality, while the dependent variable is the purchase decision. The research method used is a quantitative method with an associative approach. The population in this study was all consumers who purchased Honda motorcycles at the Astra Honda Dealership in Tanah Patah, Bengkulu City. The sampling technique used purposive sampling with a sample size of 150 respondents. Data collection was carried out through a questionnaire using a Likert scale. The data analysis method used was Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS 4 software.The results showed that brand equity had a positive and significant influence on the purchase decision for Honda motorcycles at the Astra Honda Dealership in Tanah Patah, Bengkulu City. Product quality also had a positive and significant influence on purchase decisions. Furthermore, brand equity and product quality simultaneously significantly influenced consumer purchase decisions. This indicates that the better consumers' perceptions of Honda brand equity and product quality, the higher their purchase decisions. Keywords: Brand Equity, Product Quality, Purchase Decision, Astra Honda Dealership.